2002
DOI: 10.1107/s0907444902016621
|View full text |Cite
|
Sign up to set email alerts
|

ACORN in CCP4 and its applications

Abstract: ACORN is a comprehensive and ef®cient phasing procedure for the determination of protein structures when atomic resolution data are available. Reliable phases can be developed from a fragment composed of a small percentage (less than 5%) of the scattering matter of the unit cell. For example, ACORN has been used to solve a structure of 1093 atoms from only one S atom. The map from ACORN typically reveals the 90% of whole structure. The initial model can be automatically built using ARP/wARP or QUANTA. ACORN ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…For voxels with high V, is replaced by [ 4 /( 2 2 () + 2 )] 1/2 [with usually 0.5 and where 2 () is the variance of the density over the whole cell] if positive and by zero if negative. This has a similar effect to the procedure used in the CCP4 program ACORN (Yao, 2002), which however applies the same procedure to all voxels. For intermediate values of V a suitably weighted mixture of the two treatments is used.…”
Section: The Sphere-of-influence Algorithmmentioning
confidence: 99%
“…For voxels with high V, is replaced by [ 4 /( 2 2 () + 2 )] 1/2 [with usually 0.5 and where 2 () is the variance of the density over the whole cell] if positive and by zero if negative. This has a similar effect to the procedure used in the CCP4 program ACORN (Yao, 2002), which however applies the same procedure to all voxels. For intermediate values of V a suitably weighted mixture of the two treatments is used.…”
Section: The Sphere-of-influence Algorithmmentioning
confidence: 99%
“…5 The crystal structure was solved to 1.1 Å resolution using ab initio phasing methods with the program ACORN. 6 Secondary structure predictions using the sequence of the ENT domain suggested that it was composed predominantly of a-helices. Therefore, the ACORN-MR option was used to generate normalized structure factors from the observed data and model.…”
Section: Structure Determinationmentioning
confidence: 99%
“…6 Phases were determined for the 1.1 Å data by using a 15 residue helical fragment from the CCP4 fragment library and applied to the program ACORN-MR to produce an interpretable electron density map. An atomic model was built into this phased map by docking the sequence of the protein.…”
Section: Structure Solution and Refinement Of Emsy 1-100mentioning
confidence: 99%
“…These were assumed to be primarily the sulphur atoms present in the 11 methionines and four cysteines in the crystallized protein. The determination of phases was ultimately achieved by using the set of 16 atoms located with the low energy data set as a seed atom set for ab initio phasing of the 1.08 Å resolution data and the program ACORN 17. This resulted in an outstanding set of phases that allowed rapid automated model building of a complete model [Fig.…”
Section: Resultsmentioning
confidence: 99%